Laughter-eliciting factors in Filipino preschool children - La'O, Ma. Carissa A.
This study focused on laughter-eliciting factors among 3- and 5-years old children. It aimed to determine content and causes of laughter and their amount. Thirty children in homogeneous classes were observed from the UP Child Development Center. Laughter occurrences from from videos and running records were sorted into categories of similar themes. Statistical tests such as frequency distribution and chi-square were used to highlight the qualitative material. Results revealed that the content of laughter significantly differed between genders and class comparisons. Females laughed more in Art and Creativity, Class Routines and Rules, Math and Science while males laughed more in the content of Language. Children in homogeneous classes laughed more in Language, and Class Routine and Rules whereas children in heterogeneous classes were predisposed to laugh more in Art and Creativity, Math and Science, and Physical. The cause of laughter only differed significantly between the ages of children. Younger children laughed mainly because of accomplishment as older children generally laughed more because of Play and Ridicule and Superiority Over Others. Other causes were Mistake Inferiority and Incapability of Self, and Response to Structure. The study found that five-years olds laughed 12% more, females laughed 2% more, and children in heterogeneous classes laughed 8% more than their counterparts. With these insights, recommendation were given to provide a more holistic view of the child in the preschool setting.